Acting through technology: The proliferation of open source practices and its consequences - Baack, Stefan; Velkova, Julia; Kubitschko, Sebastian; Ferrer, Raul; Handler, Reinhard (AoIR Selected Papers of Internet Research, 2016)
The internet has enabled new forms of sharing and collaboration which arguably have been pioneered by early open source communities (Coleman 2013). The availability and modifiability of the underlying technologies and infrastructures combined with the technological affordances of the internet has allowed open source advocates to use technology as a form of expression: they not only act with available technology, but through it by creating technical infrastructures that express ideas and concepts about “how economy and society should be ordered collectively” (Kelty, 2008, p. 28). Kelty (2008) described open source as an experimental system made up of five key practices: sharing source code, defining openness, writing copyright licenses, coordinating collaborations, and forming a movement. These practices can be adopted and appropriated by actors in almost every area of social life, from encyclopedic knowledge (Wikipedia) to activism (Beyer, 2014) or creativity online (Creative Commons). While there have been critical voices for some time, these practices have been regularly seen by the broader public, as well as by academia, as promoting democratic values like participation and knowledge empowerment in the digital mediascape. Much less attention has been paid to the broader consequences of this “reorientation of knowledge and power” (Kelty, 2008, p. 7), i.e. to the actual social structures expressed and promoted through such practices. Tkacz (2012) has shown that promoting openness and transparency introduces new forms of closure which are often overlooked. Drawing from Stuart Hall (1997, p. 230), we suggest that what is at stake in these developments is not a dual choice between ‘open’ and ‘closed’ forms of social organization, but a more complex transition between different modes of regulation and valuations of technologies which need to be examined carefully. This panel brings together early-career scholars that aim to shed light on how different actors in different domains of social life are acting through technology and what values and forms of social organization they promote through such practices. The first paper (A) will explore the internal social structures among producers who are radically committed to openness through sharing technology and content online. It foregrounds that in these practices, openness and sharing are not only about creating open knowledge, public digital culture and technologies, but also trigger practices of self-control, discipline, and contestation over what is to be made public and how. The author argues that the ways in which these are negotiated have implications for the broader domain of cultural production online. The next two papers each look at the social structures promoted through open source practices by exploring how actors committed to them are trying to affect institutional politics. The second paper (B) explores hacking as a politically motivated practice by showing how one of the world’s largest hacker organizations – the Chaos Computer Club (CCC) – thematizes, problematizes and ultimately politicizes technology. It demonstrates that by acting on the structural features of contemporary political constellations, the CCC is able to bring its political endeavor of politicizing technology to life. The third paper (C) explores the relatively new phenomenon of civic tech, which is about developing tools to solve civic problems by improving government services or by empowering citizens. It shows that civic tech applications do not merely describe, but aim to shape the relationship between citizens in their governments in particular ways through structures encoded in the data they utilize and collect. The final paper (D) introduces another perspective by exploring how established institutions are adapting practices and values from open source cultures, thereby expanding their existing structures and practices. It analyzes an investigative journalism story run by The Guardian that combined open data, crowdsourcing and game mechanics with the purpose of engaging readers. The case shows how news organizations are acting through technology to shift media agency by inviting the readers to take an active role in the investigation, and how such practices can reconfigure civic engagement. As acting through technology becomes more widespread, this panel emphasizes the importance of empirical and cross-disciplinary research by showing how similar practices and values from open source cultures can be used to support different modes of regulations in different areas of social life. References Beyer, J. L. (2014). The Emergence of a Freedom of Information Movement: Anonymous, WikiLeaks, the Pirate Party, and Iceland. Journal of Computer-Mediated Communication, 19(2), 141–154. Coleman, G. (2013). Coding Freedom: The Ethics and Aesthetics of Hacking. Princeton: Princeton University Press. Hall, S. (1997). The Centrality of Culture: Notes on the Cultural Revolutions of our Time. In K. A. Thompson (Ed.), Media and Cultural Regulation (1 edition, pp. 207–238). SAGE Publications Ltd. Kelty, C. M. (2008). Two Bits: The Cultural Significance of Free Software. Durham: Duke University Press. Tkacz, N. (2012). From open source to open government: A critique of open politics. Ephemera: Theory and Politics in Organization, 12(4), 386–405.